KONSEP TARBIYAH DALAM HADITS NABI: PENDEKATAN TAFSIR TEMATIK TERHADAP PENDIDIKAN KONTEMPORER - Adnan, Irfan Maulana; Wahyu Sihab; Fikri Fathul Aziz (As-Sulthan Journal of Education, 2025)
This study explores the concept of tarbiyah in the hadith of Prophet Muhammad SAW and its relevance to contemporary education. Using a qualitative methods and literature review, the research finds that tarbiyah serves not only as an educational process but also encompasses the development of individual character and morality. The results indicate that the integration of tarbiyah values into modern educational curricula is crucial for creating a holistic learning environment that nurtures both the intellect and the spirit of students. Furthermore, the role of educators as exemplars in applying the principles of tarbiyah is key to shaping a generation that is both intelligent and morally upright. This study also identifies various challenges and opportunities in implementing tarbiyah in the modern era, particularly in the context of globalization and technological advancements. It emphasizes the importance of continuous evaluation in the learning process to ensure the effectiveness of educational practices. By applying the principles of tarbiyah, it is hoped that education can produce individuals who excel academically while also possessing integrity, strong moral character, and high social awareness, contributing positively to society.